PENGARUH PERCEIVED USEFULNESS, PERCEIVED EASE OF USE TERHADAP PURCHASE INTENTION DAN ATTITUDE TOWARD USING SEBAGAI MEDIASI - AlBanani, Muhammad Tsabit; Hapsari, Raditha Dwi Vata (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Changes of people’s lifestyle from traditional to modern has made startup businesses develop rapidly. This should be addressed well by Shopee by improving the quality of their application. The objective of this research is to identify the effects of perceived ease of use and perceived usefulness on the intention of Anwarul Huda Islamic Boarding School’s students in Malang city to purchase via Shopee with the mediation of attitude toward using. The sample of this explanatory research was selected using saturated sampling, resulted in 144 respondents. The data was harvested through Likert-scaled questionnaires and was assessed using Outer Model, Inner Model, and Mediation Tests in SmartPLS 3.0. The data assessment results show that, from the direct effect testing to five variables, there are two test results that do not have any effect; they are Perceived Ease of Use (PEOU) on Attitude Toward Using and Perceived Usefulness (PU) on Purchase Intention (PI). From the indirect effect testing to two variables, there is one testing result that does not have any effect; that is Perceived Ease of Use (PEOU) on Purchase Intention (PI) through Attitude Toward Using as the mediator. Therefore, Shopee should consider the use of marketing strategies that include feature development and enhancement in their application.